Vertex Szeged indices of P2n + FPn+1. Issue 4 (18th May 2020) - Cancan, Murat; Naeem, Muhammad; Baig, Abdul Qudair; Gao, Wei; Aslam, Aneela
Abstract: Let G= ( V, E ) be a simple connected graph, where V(G ) and E ( G ) represent the vertex set and edge set of G respectively. For a graph the vertex Szeged index is equal to the product over all edges uv of G of the number of vertices which are not equidistant to vertices u and v . The vertex Padmarker-Ivan ( PIv ) index of a graph is the sum over all edges uv of G of the number of vertices which are not equidistant to vertices u and v . The aim of this paper is to compute and compare the vertex Szeged index and vertex Padmarker-Ivan ( PIv ) index of P 2 n+F Pn +1, where P 2 n+F Pn +1 represents four operation on P 2 n × Pn +1 .